A Practical Guide to Improving School Climate in High Schools. (September 2019) - VanLone, Janet; Freeman, Jennifer; LaSalle, Tamika; Gordon, Lola; Polk, Tiffany; Rocha Neves, Jesslynn
Research focusing on school climate has shown that healthy, safe, and positive school environments are associated with improved psychological, social, behavioral, and academic outcomes for secondary students. For this reason, it is important for schools to understand how to improve perceptions of school climate through effective, evidence-based interventions. Despite the importance of school climate, secondary schools continue to struggle to implement evidence-based interventions that may improve school climate in these settings. The purpose of this guide is to provide a practical step-by-step guide for improving school climates in high schools within a multitiered system of support (MTSS) framework, specifically focusing on how to use the critical features of MTSS (i.e., outcomes, data, practices, systems) to support effective implementation.